Inducing shoppers’ impulsive buying tendency in live-streaming: integrating signaling theory with social exchange theory - Luo, Xi *; Cheah, Jun-Hwa; Lim, Xin-Jean; Ramayah, T *; Dwivedi, Yogesh K. (Emerald, 2023)
Purpose The increasing popularity of live-streaming commerce has provided a new opportunity for e-retailers to boost sales. This study integrated signaling theory and social exchange theory to investigate how streamer- and product-centered signals influence customers’ likelihood of making an impulsive purchase in the live-streaming commerce context.